Influence of blast size on the relation between ground peak particle velocity and scaled distance in open pit limestone mines – A case study - Paurush P.; Rai P.; Sharma S.K. (My University, 2025)
The present study was carried out in a limestone mines of Chhattisgarh, India to examine the effect of the number of holes detonated in a blast round on ground vibrations induced by blasting operations at different locations ranging from 100m to 370m in the mine. In this study, the trial blasts were categorized into 4 major groups depending on the number of holes fired in the blast rounds. First group consisted of up to 25 blast holes, second group of 26-50 blast holes, third group of 51-75 blast holes and fourth group consisted of 76-100 no. of blast holes. Ground vibrations in terms of peak particle velocity (PPV in mm/s) were recorded using standard seismographs in the field. Multi-variate linear regression (MLR) was carried out to determine the effect of number of holes on the PPV. Further, peak particle velocity (PPV) vs. scaled distance (SD) relationship were plotted and a comparison of the coefficient of determination (R2) was made for the data set associated with all the grouped holes and combined data set. The results of the study showed that the number of holes do not have any significant impact on the relationship obtained between ground vibration (PPV) vs SD with increasing number of holes by blasting operations in limestone mines. © 2020, Books and Journals Private Ltd.. All rights reserved.